MAHMUDKHODJA BEHBUDIY AND EDUCATIONAL REFORMS - Mirzoyeva Nigora Shavkatjonovna; Khuraslanova Raykhona Zokirbek kizi (Western European Studies, 2026)
This article highlights the role of Mahmudkhodja Behbudiy in the Uzbek Jadid movement and his reforms in the field of education. It analyzes Behbudiy's contribution to the development of the education system by establishing new-style schools, introducing modern approaches to the educational process, giving wide space to secular subjects, and preparing textbooks and methodological manuals. His activities, such as popularizing education through the press and drama, and promoting multilingual education, are also revealed in relation to their importance in the development of society.
Keywords: Mahmudkhodja Behbudiy; Jadid schools; Jadid movement